Continuation and change in Turkish foreign policy towards Syria After (2011) - بيستون عمر نورى (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
This study entitled (The consistency and shifting of the Turkish foreign policy towards Syria after 2011) is discussing on the Turkish foreign policy which has been shifting since the formation of Turkish state in 1923. There are many internal factors behind the Turkish foreign policy shifting such as; political leaders’ role, political party’s ideology, and military institutions. An enormous shifting in Turkish foreign policy has taken place since the AKP had holding power in 2002, especially moving political concern toward the Arabic countries replacing of the western countries. After Syrian uprising in 2011, Turkish foreign policy has been shifting toward the country because of geopolitical issue among two countries will effect on each other. In other word, any change in Syria will influence on Turkey. Meanwhile, Turkey behavior on Syria crisis has been inconsistent since the uprising in the country. As a result, the relationship between two countries Turkey and Syria negatively has been shifting in some areas; politically, diplomacy, economic, military and security. The reason behind Turkish behavior on Syria is related to Turkish fear on its national security, geopolitics and national interests with superpowers. However, there are some issues have been suspended between both countries due to Turkey maintains on such issues; water, İskenderun, Syria unity, ethnics and sects.